Electromagnetic Iontophoresis: A Novel Nonsurgical Method for the Treatment of Dense Vitreous and Retinal Hemorrhages - Umut Arslan; Deniz Arslan; Emin Özmert (Case Reports in Ophthalmology)
Introduction: Vitreous, retinal, and suprochoroidal hemorrhages might develop secondary to trauma, retinal tear or detachment, neovascularization due to ischemic retina. If the clearance of retinal and vitreous hemorrhages can be accelerated, more effective treatments can be planned for the underlying pathology. Case Presentations: We present 6 different cases with dense vitreous, preretinal, and subretinal hemorrhages due to Valsalva retinopathy, polypoid choroidal vasculopathy, diabetic retinopathy, neovascular age-related macular degeneration, retinitis pigmentosa with vasculitis, and myopic choroidal neovascularization. To accelerate the clearance of these dense intraocular hemorrhages, a novel nonsurgical method of electromagnetic iontophoresis (MagnoVision™) was used together with some appropriate medications in an outpatient setting without any complications or side effects. In all cases, liquefaction of the intraocular hemorrhage began by 5 days and mostly resolved by 10 days. This nonsurgical rapid clearance allowed us to diagnose and evaluate the underlying retinal and choroidal pathologies earlier and to treat them appropriately as early as possible. Conclusion: Combined use of electromagnetic iontophoresis, subtenon platelet-rich plasma and bevacizumab injection, and oral bromelain can be considered as an effective and safe new treatment method for vitreous and retinal hemorrhages without any need for surgical intervention.